Bughah Menurut Analisis Bahasa dan Syarak: Etymological and Jurisprudential Analysis of Bughah - Yusri Mohamad Ramli (RABBANICA - Journal of Revealed Knowledge, 2023)
Rebellion against the government is one of the main impetuses of radicalism and extremism that disturb public peace and tranquillity. Rebels or ‘bughah’ is the biggest criminals in Islam. This article attempts to qualitatively revisit the etymological and jurisprudential perspective of bughah by linguists and jurists to grasp the concept and overcome resistance. By library research using content analysis upon selected authoritative works of Arabic dictionaries and the Shafi’i school of law, this study concludes that bughah, in terms of language, is resistance and rebellion of a leader and government because of the act of violence and transgression. Regarding jurisprudence, resisting the government is a sin and forbidden. Bughah could only be determined if they have force, motive, and a de facto leader. In overcoming resistance, the government should prioritise discussion and compromise in making a deal to put down the insurgence while using force to eliminate the opposition. In conclusion, the understanding and process of dealing with bughah in Islamic scholarly tradition is quite a beauty. Bughah is the violence of citizens upon their leader. Thus, the leader should act firmly but forgiving, just like a father treats his rebellious child compassionately. Pemberontakan terhadap kerajaan ialah salah satu asas utama radikalisme dan ekstremisme yang merosakkan keamanan dan ketenteraman awam. Pemberontak atau ‘bughah’ ialah penjenayah terbesar dalam Islam. Artikel ini meninjau semula secara kualitatif perspektif bahasa dan syarak mengenai bughah yang dibahaskan oleh para ilmuwan bahasa dan fiqah bagi memahami konsep dan menangani pemberontakan. Melalui penelitian kepustakaan secara analisis kandungan terhadap karya muktabar terpilih daripada kamus bahasa Arab dan kitab fiqah mazhab Syafii, dapat dirumuskan bahawa bughah dari sudut bahasa ialah pemberontak dan penderhaka kepada pemimpin dan kerajaan kerana zalim dan melampau batas. Dari sudut syarak, memberontak adalah dosa dan haram dilakukan. Bughah hanya dapat ditentukan jika wujud kekerasan, niat dan pemimpin ikutan. Bagi menghadapi pemberontakan, kerajaan perlu mengutamakan perundingan dan perdamaian tatkala memerangi pemberontakan. Kesimpulannya, kefahaman dan tatakelola mengenai bughah dalam tradisi turath Islam adalah cukup cantik. Bughah jelas ialah suatu kezaliman rakyat terhadap pemimpin, justeru pemimpin perlu menanganinya secara tegas tetapi dengan penuh kemaafan seumpama bapa mengasihi anaknya yang menderhaka.